Football - Klosterman, Chuck, 1972- (Penguin Press, 2026)
"A hilarious but nonetheless groundbreaking contribution to the argument about which force shapes American life the most. For two kinds of readers--those who know it's football and those who are about to find out"-- Provided by publisher.